ANALISIS KEBIJAKAN FORMULASI HUKUM PIDANA TERHADAP UPAYA PENANGGULANGAN TIDAK PIDANA DALAM RUU ANTIPORNOGRAFI DAN PORNOAKSI - Firganefi, Firganefi (Fakultas Hukum Universitas Lampung, 2009)
The research studies about the formulation if criminal low toward the effort of criminal act prevention in the ordinance program of anti pornografi and lowsuit (Rencana Undang-Undang Anti Pornografi dan Pornoaksi/RUU APP). the research uses normatif-empirical jurisdiction approach. the result of research indicates that criminal policy in the ways of criminal act prevention included in RUU APP that is through panel and non panel lines. executive body which establishes a constitution has arranged RUU APP included its panel sanctions, so the orientation of the policy uses more panel priority in criminal act of pornografi and lowsuit prevention